2015
DOI: 10.4103/2230-8210.131761
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thyroid and gonadal function in liver diseases

Abstract: Introduction:Liver is involved with the synthesis of carrier proteins and metabolism of various hormones and liver diseases may, therefore, be associated with various endocrine disturbances. This study was conducted to assess thyroid and gonadal function in subjects with acute hepatitis (AH), chronic liver disease (CLD), and those who had undergone liver transplantation (LT).Materials and Methods:Patients with AH, CLD with Child-Pugh stage A (CLD-1) and Child-Pugh stage B or C (CLD-2), and LT seen at our terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
6
8
2
Order By: Relevance
“…On comparing the mean serum levels of FT3 in Child A, B, and C, the lowest levels were among the Child C group (1.4 ± 1.0), followed by the Child B group (1.9 ± 1.0), while the Child A group was within the normal range (2.5 ± 0.6). This is in agreement with [5], who found that serum total T3 was lower in all forms of liver disease when compared with controls. However, FT3 was significantly lower in patients with chronic liver disease, especially liver cirrhosis (Child B or C).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On comparing the mean serum levels of FT3 in Child A, B, and C, the lowest levels were among the Child C group (1.4 ± 1.0), followed by the Child B group (1.9 ± 1.0), while the Child A group was within the normal range (2.5 ± 0.6). This is in agreement with [5], who found that serum total T3 was lower in all forms of liver disease when compared with controls. However, FT3 was significantly lower in patients with chronic liver disease, especially liver cirrhosis (Child B or C).…”
Section: Discussionsupporting
confidence: 93%
“…However, it disagrees with [5], who found lower TSH levels in patients with chronic liver disease compared to controls. They suggested this was because there was an increased level of inflammatory cytokines that negatively affected the hypothalamic-thyroid axis in chronic liver disease.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The liver plays an important role in the metabolism of thyroid hormones, as it is the most important organ in the peripheral conversion of tetraiodothyronine (T4) to T3 by Type 1 deiodinase. [ 3 4 ] Type I deiodinase is the major enzyme in the liver and accounts for approximately 30%–40% of extrathyroidal production of T3, it can carry out both 5’-and 5-deiodination of T4 to T3. Moreover, the liver is involved in thyroid hormone conjugation and excretion, as well as the synthesis of thyroid binding globulin.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of ovariectomy on androgen function is controversial, but there is no dispute that androgen levels are very low in ovariectomized chickens ( Abraham et al., 1969 , Baum et al., 1978 , Nishino et al., 1998 , Turdi et al., 2015 ). Because steroid hormones have diverse activities, ovarian dysfunction is associated with a variety of pathologies, such as glucose and lipid metabolism disorders and immune system dysregulation ( Knöferl et al., 2001 , Wood et al., 2008 , Burra et al., 2010 , Kharb et al., 2015 ). Abdominal fat, insulin, and blood glucose levels are often significantly higher in ovariectomized rats, as are levels of liver lipids, total cholesterol, and triglycerides, and the effects can be reversed by estrogen replacement therapy ( Liu et al., 2004 , Wang et al., 2004 , Choi and Song, 2009 , Leite et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%